2009
DOI: 10.1536/ihj.50.377
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1 Regulates Cardiomyocyte Apoptosis by Targeting Bcl-2

Abstract: SummaryMicroRNA-1 (miR-1) is preferentially expressed in cardiac muscles, and the expression has been demonstrated to be involved in cardiac development and cardiovascular diseases. Here we report that miR-1 is closely related with ischemia/reperfusion injury in a rat model. The level of miR-1 is inversely correlated with Bcl-2 protein expression in cardiomyocytes of the I/R rat model. In vitro, the level of miR-1 was dramatically increased in response to H2O2. Overexpression of miR-1 facilitated H2O2-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
170
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(176 citation statements)
references
References 8 publications
(14 reference statements)
5
170
0
1
Order By: Relevance
“…This result is in contrast with two previous studies in myocardial cells showing an upregulation of miR-1 on H 2 O 2 exposure. 21,22 Interestingly, miR-1 is known to promote myogenic differentiation 23 and our finding on miR-1 downmodulation by H 2 O 2 is in agreement with ROS ability to inhibit myogenic differentiation. 3 miR-200 family has been extensively studied in the epithelial-to-mesenchimal transition (EMT) of cancer cells; 14 in EMT miR-200 family downmodulation enhances cancer aggressiveness and metastases, whereas reintroduction of miR-200 family miRNAs in some tumors inhibits their growth.…”
Section: Discussionsupporting
confidence: 86%
“…This result is in contrast with two previous studies in myocardial cells showing an upregulation of miR-1 on H 2 O 2 exposure. 21,22 Interestingly, miR-1 is known to promote myogenic differentiation 23 and our finding on miR-1 downmodulation by H 2 O 2 is in agreement with ROS ability to inhibit myogenic differentiation. 3 miR-200 family has been extensively studied in the epithelial-to-mesenchimal transition (EMT) of cancer cells; 14 in EMT miR-200 family downmodulation enhances cancer aggressiveness and metastases, whereas reintroduction of miR-200 family miRNAs in some tumors inhibits their growth.…”
Section: Discussionsupporting
confidence: 86%
“…11 In a recent study, the regulatory roles of miR146b-5p in erythropoiesis and megakaryopoiesis have been reported. 40 MiR-1 has BCL2 as its target, 41 and circulating miR-1 is a potential novel biomarker in acute myocardial infarction. 42 MiR-1 exhibits anti-inflammatory roles in asthma mouse models and in inflammatory myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Another group reported that the mRNA and protein levels of transforming growth factor-␤ and SMAD3 are decreased by a virus-encoded microRNA, miR-LAT (23). The mRNA and protein levels of Bcl-2 are also down-regulated by miR-1 (24). Thus, our result is not unusual and provides new evidence to support the conclusion that miRNAs regulate not only the stability and translation but also the transcription of target mRNAs; the latter is most likely via an indirect mechanism.…”
Section: Discussionmentioning
confidence: 99%